Efisiensi Penggunaan Elearning dengan Memanfaatkan Teknologi Mobile Wireless Pada Stain Parepare - Muhammad Ahsan; Bahtiar (Al-Ishlah: Jurnal Pendidikan Islam, 2018)
ABSTRACTE-learning is formal and informal learning. Formally, the e-learning learningmethod is carried out using learning that comes from the syllabus. The use ofe-learning from lecturers and students at STAIN Parepare is currently stillconsidered not to work well. The interest of students and lecturers in usinge-learning is still lacking. This is because the resources of the lecturers in filling thecontent of the e-learning are still lacking. This study aims to determine the efficiencyof using e-learning by using mobile wireless and knowing the level of satisfaction ofe-learning users by utilizing mobile wireless.